2019
DOI: 10.1111/ejn.14346
|View full text |Cite
|
Sign up to set email alerts
|

Correct expression and localization of collagen XIII are crucial for the normal formation and function of the neuromuscular system

Abstract: Transmembrane collagen XIII has been linked to maturation of the musculoskeletal system. Its absence in mice (Col13a1−/−) results in impaired neuromuscular junction (NMJ) differentiation and function, while transgenic overexpression (Col13a1oe) leads to abnormally high bone mass. Similarly, loss‐of‐function mutations in COL13A1 in humans produce muscle weakness, decreased motor synapse function and mild dysmorphic skeletal features. Here, analysis of the exogenous overexpression of collagen XIII in various mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…2), similar to what happens in NMJ development [176]. Of note, the composition and regulation of the surrounding extracellular matrix will also have a key role in the proper functioning of the NMJ [177].…”
Section: Agrin-muskmentioning
confidence: 70%
“…2), similar to what happens in NMJ development [176]. Of note, the composition and regulation of the surrounding extracellular matrix will also have a key role in the proper functioning of the NMJ [177].…”
Section: Agrin-muskmentioning
confidence: 70%
“…In the light of data obtained with cells and mutant mice (Hägg et al 1998(Hägg et al , 2001Kvist et al 2001;Sund et al 2001;Tahkola et al 2008;Tuomisto et al 2008), collagen XIII appears to play a role in cell-matrix adhesion. Recent in vivo studies highlight involvement of collagen XIII in the development, differentiation, and maturation of musculoskeletal tissues and vessels and in maintaining tissue integrity (Latvanlehto et al 2010;Härönen et al 2017;Zainul et al 2018;Heikkinen et al 2019;Koivunen et al 2019). The 150-nm flexible ectodomain of collagen XIII can potentially cross the basement membrane around myofibrils or under endothelium and can penetrate into the surrounding stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen XIII is broadly distributed in mesenchymal tissues at low levels (Hägg et al 2001;Sund et al 2001;Sandberg et al 1989;Juvonen et al 1992;Sandberg-Lall et al 2000). Many studies with genetically modified mice have indicated its physiological functions in musculoskeletal tissues (Ylönen et al 2005;Härönen et al 2017Härönen et al , 2019Zainul et al 2018;Koivunen et al 2019) and congenital myasthenic syndrome type 19 (CMS19; OMIM #616,720) musculoskeletal phenotypes (Logan et al 2015;Rodriguez Cruz et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Tiga molekul terakhir adalah komponen NMJ sehingga kolagen mungkin berperan dalam menstabilkan dan pematangan NMJ (neuromuscular junction). Apabila kolagen ini tidak ada pada mencit maka menyebabkan gangguan diferensiasi dan fungsi NMJ [69].…”
Section: Pematangan Neuromuscular Junctionunclassified